Peranan Guru Dalam Proses Pembelajaran Bahasa Indonesia Di SD Inpres Komboi Kabupaten Biak Numfor - Ana Albartina Dasem; Beatus Mendelson Laka; Amelia Niwele (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2018)
The purpose of this study is to know and describe the role of teachers in the learning process in Primary School of Indonesia Inpres Komboi Biak Numfor District. This research uses qualitative research methods with the process of collecting data using interviews, observation and questionnaires. The place of this research is SD Inpres Komboi Biak Numfor District. The sample of this study amounted to 36 people consisting of 30 students and 6 teachers. For sample student researcher use random sampling technique (random). The results of this study indicate that in general teachers who teach in elementary school Inpres Komboi, already carry out their duties and roles well but the obstacles that exist in elementary school Inpres Komboi still less support books books such as packages in the process of learning Indonesian.